Meta-analysis: proton pump inhibitors moderately increase the risk of small intestinal bacterial overgrowth - Su, Tingting; Lai, Sanchuan; Lee, Allen; He, Xingkang; Chen, Shujie (Journal of gastroenterology, 2018)
The use of proton pump inhibitors (PPIs) may potentially predispose to the development of small intestinal bacterial overgrowth (SIBO), but this association is controversial due to conflicting results from studies conducted to date. The aim of this meta-analysis was to evaluate the association between the use of PPIs and the risk of SIBO. We systematically searched the online PubMed, Embase, and Cochrane Library databases and Web of Science for relevant articles published up to November 2016. Two researchers identified and extracted data independent of each other. The pooled analysis was performed using the generic inverse-variance random-effects model. Subgroup and sensitivity analysis were conducted to assess the stability and heterogeneity of the pooled results. The risk of publication bias was evaluated by assessing for funnel plot asymmetry and by Egger’s test and Begg’s test. A total of 19 articles met the eligibility criteria for the meta-analysis, reporting on 7055 subjects. The pooled odds ratio (OR) showed a statistically significant association between increased risk of SIBO and PPI use (OR 1.71, 95% confidence interval 1.20–2.43). Subgroup analyses demonstrated an association between SIBO and PPI use in studies that employed small bowel aspirates culture and glucose hydrogen breath tests (GHBT) as diagnostic tests for SIBO. Our meta-analysis suggests that the use of PPI moderately increases the risk of SIBO, thereby highlighting the need for appropriate prescribing of PPIs.